Healthcare professionals' experiences with highly qualified nurses working in acute care teams in primary healthcare settings - Stine Emilie Junker Udesen; Annmarie Touborg Lassen; Nina Andersen; Christina Østervang; Dorthe Suanne Nielsen (Taylor & Francis Group, 2021)
Objective Strengthening primary healthcare with highly qualified nurses in acute care units or teams is a new Danish initiative intended to detect acute diseases and the deterioration of chronic diseases and to develop treatment for outpatients. This study explores healthcare professionals' experiences with this initiative. Design Qualitative semi-structured interviews conducted in 2019-2020. Analysis was conducted with a systematic text condensation. Setting This study is based on an acute care team in one Danish municipality called Acute Team Odense (ATO). ATO delivers acute nursing in patients' own homes (including nursing homes) in collaboration with different healthcare professionals. Subjects Individual interviews with general practitioners (GPs) (n = 15), five focus-group interviews with nurses and nursing assistants from the municipality (n = 19) and one focus-group interview with staff from the emergency department (ED) (n = 10). Main outcomes Experiences of different healthcare professionals' experiences with ATO. Results In general, all of the participants were very satisfied with the new acute care team and the cross-sectorial possibilities. The GPs usually referred ATO to assessments in which paraclinical equipment, competencies, accessibility, response time and communication were important. The municipal nurses and nursing assistants tended to use ATO if they needed second opinions or acute nurse assistance. The ED most often used ATO to assist with intravenous therapy after an ED visit. All participants reported that ATO increased what could be assessed and treated in patients' homes, which is central to preventing unnecessary hospitalisations. Conclusions ATO created new possibilities in patient's homes which potentially might prevent unnecessary hospitalisations.KEY POINTS Acute care units or teams are mandatory in Danish health care, but limited knowledge in the area is found. Healthcare professionals found that the acute care teams provided new possibilities to assess and treat patients in their own homes. Healthcare professionals experienced that the acute care team potentially prevented hospitalisations by fast clinical nurse assessments with paraclinical tests.